Nanoporous gold: A review and potentials in biotechnological and biomedical applications. Issue 8 (9th February 2021) - Xiao, Sa; Wang, Shuangjue; Wang, Xia; Xu, Ping
Abstract: Nanoporous gold (NPG) is one of the representatives of emerging materials that combine the advantages of nano, porous, and metallic materials. In addition to the general characteristics of nanoporous materials, NPG also has many unique properties, such as excellent structural stability, adjustable pore size, high conductivity, remarkable biocompatibility, clean surface, easy recycle and reuse, and unique electrochemical catalytic activities. These performances endow NPG promising application potentials in the fields of catalysis, environmental monitoring, energy storage, biomedicine, etc. Herein, this review summarizes the recent advances of NPG over the past decade. Besides preparation and modification of NPG, special emphasis is placed on its applications in biotechnology and biomedicine: catalysis, biosensors, biofuel cells, and drug delivery. The significant and representative studies in each area are comprehensively reviewed and analyzed as a reference for researchers working in related areas. The main challenges and future opportunities of NPG in these areas are also discussed. Abstract : In summary, this review not only briefly introduces the preparation, characterization, and modification of NPG, but also comprehensively analyzes the representative research results of NPG in the fields of biotechnology and biomedicine: catalysis, biosensors, biofuel cells, and drug delivery. In addition, the main challenges and future opportunities of NPG in these fields are analyzed.